2018
DOI: 10.1080/1828051x.2018.1452055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three commercial rapid kits to detect Cryptosporidium parvum in diarrhoeic calf stool

Abstract: The aim of this study was to evaluate three commercially available rapid immunochromatographic tests for detection of Cryptosporidium parvum antigens in faeces of naturally infected neonatal diarrhoeic calves. FASTest V R CRYPTO strip, FASTest V R CRYPTO-GIARDIA Strip and TETRASTRIPS V R were compared for their sensitivity, specificity, positive predictive value and negative predictive value using a cumulative positivity as gold standard. In addition, the agreement between each test and the gold standard was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…E p i d e m i o l o g i c a l s t u d i e s o n t h e p r e s e n c e o f Cryptosporidium spp. in Italian cattle farms are still limited; prevalences ranging from 5 to 11.4% (Merildi et al 2009;Duranti et al 2009;Di Piazza et al 2013) have been reported, although the percentage of positives increases (50-62.1%) when only diarrhoeic calves are considered (Grana et al 2006;Papini et al 2018). At least five Cryptosporidium species, including C. bovis, C. ryanae, C. ubiquitum and C. hominis, have been identified in cattle from Italy, but C.…”
Section: Introductionmentioning
confidence: 99%
“…E p i d e m i o l o g i c a l s t u d i e s o n t h e p r e s e n c e o f Cryptosporidium spp. in Italian cattle farms are still limited; prevalences ranging from 5 to 11.4% (Merildi et al 2009;Duranti et al 2009;Di Piazza et al 2013) have been reported, although the percentage of positives increases (50-62.1%) when only diarrhoeic calves are considered (Grana et al 2006;Papini et al 2018). At least five Cryptosporidium species, including C. bovis, C. ryanae, C. ubiquitum and C. hominis, have been identified in cattle from Italy, but C.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous diagnostic techniques have been used to detect Cryptosporidium infection in humans and animals. They include the use of faecal smears stained by the modified Ziehl-Neelsen technique, Enzyme-linked immunosorbent assays (ELISA) and polymerase chain reaction (PCR) assays [13][14]. A comprehensive overview into the detection and molecular characterization of Cryptosporidium has been described elsewhere [15] The above mentioned methods have drawbacks such as being time-consuming and relatively expensive, as well as requiring well-equipped laboratories and well-trained or skilled personnel [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…CGE, Crypto/Giardia Duo-Strip, RIDA QUICK Cryptosporidium/Giardia/Entamoeba Combi and Giardia/Cryptosporidium Quik Check the authors observed varying sensitivities ranging from 92 to 100% and 100% specificities for all RDT brands for the detection of Cryptosporidium when compared to ELISA, microscopy, and qPCR as gold standards [17]. In addition, these RDTs demonstrate varying performances, and some of them are not well validated for the detection of less frequent non-parvum/hominis Cryptosporidium species [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations